Structural divergence of chromosomes between malaria vectors Anopheles lesteri and Anopheles sinensis. Issue 1 (December 2016) - Liang, Jiangtao; Cheng, Biao; Zhu, Guoding; Wei, Yun; Tang, Jianxia; Cao, Jun; Ma, Yajun; Sharakhova, Maria; Xia, Ai; Sharakhov, Igor
Abstract Background Anopheles lesteri andAnopheles sinensis are two major malaria vectors in China and Southeast Asia. They are dramatically different in terms of geographical distribution, host preference, resting habitats, and other traits associated with ecological adaptation and malaria transmission. Both species belong to theAnopheles hyrcanus group, but the extent of genetic differences between them is not well understood. To provide an effective way to differentiate between species and to find useful markers for population genetics studies, we performed a comparative cytogenetic analysis of these two malaria vectors. Results Presented here is a standard cytogenetic map forAn. lesteri, and a comparative analysis of chromosome structure and gene order betweenAn. lesteri andAn. sinensis . Our results demonstrate that much of the gene order on chromosomes X and 2 was reshuffled between the two species. However, the banding pattern and the gene order on chromosome 3 appeared to be conserved. We also found two new polymorphic inversions, 2Lc and 3Rb, inAn. lesteri, and we mapped the breakpoints of these two inversions on polytene chromosomes. Conclusions Our results demonstrate the extent of structural divergence of chromosomes betweenAn. lesteri andAn. sinensis, and provide a new taxonomic cytogenetic tool to distinguish between these two species. Polymorphic inversions ofAn. lesteri could serve as markers for studies of the population structure and ecological adaptations of this major malaria vector.